Optimizing ITER Power Supplies Operation Through RAMI and Standardization - Sagot, François; Houtte, Didier van; Okayama, Katsumi; Hourtoule, Joel; Song, Inho (Fusion science and technology, 2011)
As the next step in the development of fusion energy, ITER has to be safe, reliable and available whenever needed to produce the experimental data as defined by the scientific program. To ensure the success of this mission, a Reliability, Availability, Maintainability and Inspectability (RAMI) analysis is being performed on the ITER plant systems to optimize the design and prepare both operation and maintenance over the ITER life. This analysis relies on a functional breakdown translated to Reliability Block Diagrams (RBDs) and on a Failure Modes, Effects and Criticality Analysis (FMECA) to provide reliability and availability calculations, to highlight the technical risks and to prioritize the ways to mitigate them in order to maximize the availability of the machine for plasma operation. Standardization is one way of addressing this concern in a cost-effective manner, as reducing the diversity of components allows keeping a reduced stock of interchangeable spares available on short notice and reducing the time to repair after a failure. This paper will present this approach as it is applied on the ITER power supplies systems: the Coil Power Supply and Distribution System (CPSDS) and the Steady-State Electrical Network (SSEN).